The Impact of Synthetic Pesticide Applications on Public Health - Ambar Susanti; Muhammad Hoesain; Sigit Prastowo (AGARICUS: Advances Agriculture Science & Farming, 2022)
Pesticides are considered as a savior of farmers in the implementation of agricultural cultivation. The practical and effective nature of using pesticides makes it easier for farmers to eradicate plant pests. The existence of a synthetic insecticide, namely DDT (Dichoro Diphenyl Trichlorethane), became a revolution in pest control techniques, which rely on the use of pesticides. Pesticides can increase agricultural production and other supporting commodities such as fisheries and livestock. Large-scale agricultural producers to small farmers with a narrow area are depend on pesticides. However, it also causes damage to the pest ecosystem based on the food chain. It has an impact on human health, such as disability, growth disorders, and even death. Human health and environmental issues related to pesticide handling are often reported in the largest synthetic pesticide user countries, including Indonesia. The accumulation of chemical pesticide compounds causes environmental pollution residues, due to their use in the community. On the other hand, farmers and agricultural actors very often neglect the use of adequate personal protective equipment and safety labels. Based on the very broad impact of pesticides on health, preventive measures are needed to help them so as not to experience pesticide poisoning, including regulation of Pesticide Tolerance Limits for pesticide products that will be traded, and providing information/counseling about pesticide applications in a measurable and safe manner. Proper direction and use are needed in the use of doses, concentrations, timing of pesticide application, and safe use with discipline in the use of Personal Protective Equipment (PPE)..